Measurement of Carbon Footprint at National University of Costa Rica for 2012-2014. Heading for Carbon Neutrality - Chavarría-Solera, Fabián; Molina-León, Óscar Mario; Gamboa-Venegas, Rebeca; Rodríguez-Flores, Jeison (Uniciencia, 2016)
Quantifying and measuring environmental indicators such as carbon footprint allows to plan measures aimed towards an improvement of the conditions that are conducive to a positive impact on the environment, minimizing or mitigating emissions of carbon dioxide and other gases that accelerate the greenhouse effect. The National University of Costa Rica (UNA, in Spanish) seeks to make the annual measuring of this indicator, in order to implement policies and actions that integrate the entire university population routed to a good sustainable development of the institution. In that sense, parallel to the raised national goal of carbon neutrality, UNA seeks to contribute in efforts to mitigate, minimize or compensate the environmental impact, with a comprehensive commitment of its staff and its students. The objective of this study is to quantify and update carbon footprint at UNA for the 2012-2014 period, to be able to analyze and compare its behavior through time, according to the applicable aspects referred to in the calculation. For the inventory of greenhouse gases (GHG) the methodology applied was endorsed by the National Meteorological Institute (IMN, for its initials in Spanish), using timekeeping factors, specified in the Manual of Greenhouse Gases Emission Factors, in its fourth edition, 2014. As a result, between the years 2012 to 2014 a 22% increase of carbon footprint was obtained, going from the equivalent of 2,906 to 3,568 tonnes of CO2. The above due to increases in various aspects, as the number of people in the institution, as well as the pollution emitted by air travel. The intention of these results is to identify increases or decreases in emissions and establish strategies or specific environmental measures for their reduction.